Refugees and the rule of law in Ireland - Brazil, Patricia (Trinity College (Dublin, Ireland). School of Law, 2015)
This thesis is concerned with refugees and the rule of law in Ireland. Although Ireland acceded to the Convention Relating to the Status of Refugees in 1956, and the 1967 Protocol to that Convention in 1968, refugee law is a relatively new feature of the legal landscape in this jurisdiction. Until the 1990s, the numbers of people seeking asylum in Ireland were negligible, a fact reflected in the limited consideration of this topic in both academic commentaries and judicial decisions up to that time. However, this situation dramatically changed from the early 1990s onwards, when the numbers seeking recognition as refugees in the State dramatically increased, placing extreme pressure both on the administrative structures and judicial institutions engaged in this process. In the past twenty years, the pace of development in refugee law in this jurisdiction has at times been staggering. The Refugee Act, passed in 1996, sought to provide for the first time in Irish law a comprehensive statutory framework governing all aspects of the refugee process. However, the Act was not fully commenced until 2001, by which time it had already been amended in a number of key ways by intervening legislation. Within five years of the full commencement of the Refugee Act, the government was already committing to a new legislative code in this area; a new Immigration, Residence and Protection Bill was first proposed in 2005 but a full draft was not published until 2008 and despite repeated government commitments to the prioritisation of this legislation, little progress has been made with the enactment of this fundamental reform since then. ...
Embargo End Date: 2020-07-01
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin, 2015